ACTIVATE-2: A Double-Blind Randomized Trial of BCG Vaccination Against COVID-19 in Individuals at Risk - Tsilika, Maria; Taks, Esther; Dolianitis, Konstantinos; Kotsaki, Antigone; Leventogiannis, Konstantinos; Damoulari, Christina; Kostoula, Maria; Paneta, Maria; Adamis, Georgios; Papanikolaou, Ilias; Stamatelopoulos, Kimon; Bolanou, Amalia; et al. (Frontiers in Immunology, 2022)
In a recent study of our group with the acronym ACTIVATE, Bacillus Calmete- Guérin (BCG) vaccination reduced the occurrence of new infections compared to placebo vaccination in the elderly. Most benefit was found for respiratory infections. The ACTIVATE- II study was launched to assess the efficacy of BCG vaccination against COVID-19. In this multicenter, double- blind trial, 301 volunteers aged 50 years or older were randomized (1:1) to be vaccinated with BCG or placebo. The trial end points were the incidence of COVID-19 and presence of anti-SARS-CoV-2 antibodies, which were both evaluated through 6 months after study intervention. Results revealed 68% relative reduction of the risk to develop COVID-19, using clinical criteria or/and laboratory diagnosis, in the group of BCG-vaccine recipients compared with placebo-vaccinated controls, during a 6-months follow-up (OR 0.32, 95% CI 0.13-0.79). ). In total, eight patients were in need of hospitalization for COVID-19; six in the placebo group and two in the BCG group. Three months after study intervention, positive anti-SARS -CoV-2 antibodies were noted in 1.3% of volunteers in the placebo group and in 4.7% of participants in BCG-vaccinated group. These data indicate that BCG vaccination has a favorable safety profile and ensures protection against COVID-19 among elderly. BCG vaccination would be a promising approach against COVID-19 pandemic.